2020
DOI: 10.5194/acp-20-14303-2020
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of PM<sub>2.5</sub>-bound polycyclic aromatic hydrocarbons in summer Beijing (China) and Delhi (India)

Abstract: Abstract. Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants in air, soil, and water and are known to have harmful effects on human health and the environment. The diurnal and nocturnal variations of 17 PAHs in ambient particle-bound PAHs were measured in urban Beijing (China) and Delhi (India) during the summer season using gas-chromatography–quadrupole time-of-flight mass spectrometry (GC-Q-TOF-MS). The mean concentration of particles less than 2.5 µm (PM2.5) observed in Delhi was 3.6 times hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…As shown in Figure 4, the distributions of modeled ∑15PAHs ( r s = 0.98; p < 0.001), cPAHs ( r s = 0.94; p < 0.001), and BaPeq‐ cPAHs concentration (0.09 ± 0.05 ng/m 3 ) agreed well with measured residential indoor exposures. From this study conducted in Hong Kong, average BaPeq concentrations in ambient and indoor settings were comparable or higher than those in Los Angeles, California (0.07 ng/m 3 ), Houston, Texas (0.03 ng/m 3 ) 21 ; Grenoble, France (0.07 ng/m 3 ), but significantly lower than those in Chinese cities (e.g., BaPeq ‐cPAHs : 1.47 ng/m 3 , BaPeq ‐15PAHs : 2.3 ng/m 3 in Beijing) 19,61 . Carcinogenic PAHs and BaPeq‐ cPAHs exposure concentrations in some residential indoor Hong Kong locations were higher than those of ambient concentrations, demonstrating the potential risk of indoor pollution to human health.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…As shown in Figure 4, the distributions of modeled ∑15PAHs ( r s = 0.98; p < 0.001), cPAHs ( r s = 0.94; p < 0.001), and BaPeq‐ cPAHs concentration (0.09 ± 0.05 ng/m 3 ) agreed well with measured residential indoor exposures. From this study conducted in Hong Kong, average BaPeq concentrations in ambient and indoor settings were comparable or higher than those in Los Angeles, California (0.07 ng/m 3 ), Houston, Texas (0.03 ng/m 3 ) 21 ; Grenoble, France (0.07 ng/m 3 ), but significantly lower than those in Chinese cities (e.g., BaPeq ‐cPAHs : 1.47 ng/m 3 , BaPeq ‐15PAHs : 2.3 ng/m 3 in Beijing) 19,61 . Carcinogenic PAHs and BaPeq‐ cPAHs exposure concentrations in some residential indoor Hong Kong locations were higher than those of ambient concentrations, demonstrating the potential risk of indoor pollution to human health.…”
Section: Resultsmentioning
confidence: 71%
“…From this study conducted in Hong Kong, average BaPeq concentrations in ambient and indoor settings were comparable or higher than those in Los Angeles, California (0.07 ng/m 3 ), Houston, Texas (0.03 ng/m 3 ) 21 ; Grenoble, France (0.07 ng/m 3 ), but significantly lower than those in Chinese cities (e.g., BaPeq -cPAHs : 1.47 ng/m 3 , BaPeq -15PAHs : 2.3 ng/m 3 in Beijing). 19,61 Carcinogenic PAHs and BaPeq-cPAHs exposure concentrations in some residential indoor Hong Kong locations were higher than those of ambient concentrations, demonstrating the potential risk of indoor pollution to human health. Other studies revealed similar findings; for instance, Wang et al 62 (2020) reported higher BaPeq concentrations indoors (e.g., dormitory, office, and laboratory) than the ambient air in Wuhan, China.…”
Section: Estimation Of Inhalation Cancer Risksmentioning
confidence: 96%
See 1 more Smart Citation
“…Partial least squares regression (PLSR) is a supervised regression extension of PCA, which models the variation in the data which is associated with a predefined sample classification (Eriksson et al, 2013). PLSR models were constructed for each individual OP assay and season to examine the most specific markers associated with seasonal assay response.…”
Section: Multivariate Modelling Of Op From Measured Componentsmentioning
confidence: 99%
“…However, approximately 60 % of total NMVOC emissions from India in 2010 were estimated to be due to solid-fuel combustion (Sharma et al, 2015). Other studies have also suggested that burning may lead to enhanced concentrations of pollutants such as polycyclic aromatic hydrocarbons in Delhi (Elzein et al, 2020). A need has therefore been identified to measure local source profiles to allow for evaluation with activity data to better understand the impact of unaccounted and unregulated local sources (Pant and Harrison, 2012).…”
Section: Introductionmentioning
confidence: 99%